AB0460 Long-term drug survival of etanercept vs other tnf inhibitor therapies in patients with rheumatoid arthritis. (12th June 2018) - Emery, P.; Vlahos, B.; Szczypa, P.; Thakur, M.; Jones, H.E.; Woolcott, J.; Santos Estrella, P.V.; Gibofsky, A.; Rolland, C.; Citera, G.; Marshall, L.
Abstract : Background: TNFα inhibitors have profoundly altered outcomes for patients with rheumatoid arthritis (RA) since they were introduced >15 years ago, by reducing disease activity and radiographic progression and improving quality of life. As a chronic disease, RA often requires life-long treatment, understanding drug survival in real-world settings can be beneficial in optimising disease management. Objectives: To compare the long-term drug survival of adalimumab (ADA), certolizumab pegol (CZP), etanercept (ETN), golimumab (GLM), and infliximab (IFX) in patients with RA based on systematic literature review (SLR). Methods: In this SLR, the goal was to identify full-text articles containing registry data or systematic reviews on TNFα inhibitors, following Cochrane dual-reviewer methodology. Searches were conducted in November 2017 with no date restriction, using Embase ®, MEDLINE ®, the Cochrane Central Trials Register and Database of Systematic Reviews, other Cochrane Library databases, and PubMed. Outcomes extracted included drug survival data that were analysed and reported using Kaplan-Meyer or Cox regression methods. Results: Of 3688 non-duplicated publications initially identified, 3299 were excluded based on titles or abstracts and 344 based on full-text screening, leaving 26 publications published between 2005 and 2017 included in the analysis. The number of studies (range of sample size) for each drug were ADA: 15 (25–2349), ETN: 17 (20–3892), IFX: 21 (26–2898), GLM: 4 (2–88) and CZP: 1 (N/A). Among the analysed studies, the mean disease duration in years (range) was ADA: 10.7 (8.2–15.1); ETN: 15.9 (5.0–18.5); IFX: 14.2 (8.5–19.3); CZP: 10.3 (N/A); GLM: 8.9 (8.1–11.5) and mean baseline DAS28 (range) was ADA: 5.0 (4.2–5.9), ETN: 5.2 (4.3–6.3), IFX: 5.3 (4.1–6.4); CZP: 4.7 (N/A) and GLM: 4.7 (4.1–5.1). Trends for survival rates of first-line ETN were slightly higher than ADA at time points≥36 months; ADA and ETN had higher survival rates than IFX at >48 months (figure 1). Conclusions: Long-term survival rates for ADA, ETN, and IFX were similar and relatively high for treatment periods up to 36 months. After 36 months, there was a noticeable decline in drug survival for all three TNFα inhibitors. Heterogeneity in study size and design may contribute to the range of survival data for each agent. Disclosure of Interest: P. Emery Consultant for: Pfizer, MSD, Abbvie, BMS, UCB, Roche, Novartis, Samsung, Sandoz and Lilly, B. Vlahos Shareholder of: Pfizer, Employee of: Pfizer, P. Szczypa Shareholder of: Pfizer, Employee of: Pfizer, M. Thakur Shareholder of: Pfizer, Employee of: Pfizer, H. Jones Shareholder of: Pfizer, Employee of: Pfizer, J. Woolcott Shareholder of: Pfizer, Employee of: Pfizer, P. Santos Estrella: None declared, A. Gibofsky Shareholder of: AbbVie, Angen, Celgene, Pfizer, GSK, J and J, Regeneron, Consultant for: AbbVie, Celgene, MSD, Pfizer, Iroko, Horizon, Samumed, Relburn, Sandoz, Speakers bureau: Amgen, AbbVie, Pfizer, Celgene, Iroko, Horizon, MSD, Novartis, C. Rolland Employee of: Envision Pharma Group, G. Citera Consultant for: Pfizer, AbbVie, Bristol Myers Squibb, Novartis, Roche, L. Marshall Shareholder of: Pfizer, Employee of: Pfizer